Tapinarof Improved Outcomes and Sleep for Patients and Families in Two Phase 3 Atopic Dermatitis Trials in Adults and Children - Eric L. Simpson; Adelaide A. Hebert; John Browning; Rocco T. Serrao; Howard Sofen; Philip M. Brown; Stephen C. Piscitelli; David S. Rubenstein; Anna M. Tallman (Dermatology and Therapy)
Abstract Introduction Tapinarof is a topical aryl hydrocarbon receptor (AhR) agonist in development for the treatment of atopic dermatitis (AD). In two phase 3 trials (ADORING 1 and 2), tapinarof cream 1% once daily (QD) demonstrated significant efficacy and was well tolerated in patients down to age 2 years with AD. Here, we evaluate patient-reported outcomes (PROs), including family impact, with tapinarof in ADORING 1 and 2. Methods In ADORING 1 and 2, 813 patients were randomized to tapinarof or vehicle QD for 8 weeks. PROs were assessed using the Dermatology Life Quality Index (DLQI), Children’s Dermatology Life Quality Index (CDLQI), Infants’ Dermatitis Quality of Life Index (IDQOL), Dermatitis Family Impact Questionnaire (DFI), and Patient Oriented Eczema Measure (POEM). Results Mean baseline DLQI, CDLQI, IDQOL, and DFI scores indicated that the impact on families and patients’ quality of life (QoL) of AD was moderate to very large. Mean POEM scores indicated moderate to severe AD symptoms at baseline. Tapinarof improved QoL versus vehicle across all endpoints at week 8: DLQI, − 6.2 vs − 3.5 (P = 0.0031) and − 5.5 vs − 3.5 (P = 0.0028); DFI, − 5.6 vs − 2.9 (P < 0.0001) and − 5.6 vs − 3.8 (P = 0.0037), in ADORING 1 and 2, respectively. Similar improvements in CDLQI and IDQOL were reported with tapinarof versus vehicle. Tapinarof also significantly improved CDLQI, DFI, and POEM sleep subdomain scores versus vehicle. POEM scores also improved with tapinarof versus vehicle: ≥ 12 years, − 9.4 vs − 5.3 and − 10.6 vs − 3.6 (both P < 0.0001); < 12 years, − 11.4 vs − 5.7 (P < 0.0001), and − 10.8 vs − 7.3 (P = 0.0005). Conclusions Tapinarof significantly improved QoL across PROs, including sleep and family impact, regardless of age, from week 1 (the earliest evaluation) through week 8. Tapinarof is a once-daily, non-steroidal cream that rapidly improves AD symptoms, sleep, and QoL in patients down to age 2 years with AD. Trial Registration Clinical Trials.gov identifier: NCT05014568; NCT05032859.